"Todos os brasileiros comem o mesmo café da manhã?" - Perspectivas interculturais nos cadernos de apoio de língua inglesa do currículo paulista para o ensino fundamental - Blandino, Paulo Rogério (Universidade Federal de São Carlos, 2022)
This research aims to verify the concept of interculturality present in the activities of the English textbooks for the last years of elementary education of the São Paulo Curriculum. Therefore, and with regard to the theme of interculturality, the works of Tubino (2005), Maher (2007), Candau (2008), Walsh (2010) and Piller (2017) were used as a theoretical framework. Considering that in the official text of the São Paulo Curriculum (SÃO PAULO, 2019) interculturality is seen as a direct result of teaching English as a lingua franca (ELF), the theoretical framework was complemented by works related to this theme (CANAGARAJAH, 2013; JENKINS, 2005, 2009, 2015, 2017; JENKINS; COGO; DEWEY, 2011; LEFFA, 2006; MOITA LOPES, 2008; ROSA, 2021; SEIDLHOFER, 1999, 2001, 2005, 2009; SEIDLHOFER; WIDDOWSON, 2017; SIQUEIRA, 2011). Regarding the methodology, and based on the classification proposed by Paiva (2019), the research was characterized as being qualitative in nature, descriptive and documentary in relation to research methods, inserted in the area of social sciences, within the field of Applied Linguistics and having as source of information the official documents of the São Paulo state Curriculum and the Common Core Curriculum (BNCC), as well as the English textbooks for the last years of elementary education, from which the activities for the analysis were selected. Based on the theoretical discussions held about the terms culture, multiculturalism and ELF, and relating them to the categorization of interculturality proposed by Walsh (2010), it was verified that in the activities there are characteristics of the three perspectives of interculturality: relational, functional and critical, and not only of the latter, considered as the closest to the conception of interculturality presented by the São Paulo Curriculum.
"Do all brazilian people have the same breakfast?" - Intercultural perspectives in the English textbooks for the last years of elementary education of the São Paulo curriculum
Keywords: Ensino e aprendizagem de línguas; Interculturalidade; Língua inglesa; Diretrizes oficiais; Ensino fundamental; Language teaching and learning; Interculturality; English language; Official guidelines; Elementary education; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::LINGUISTICA APLICADA